Visual C++ 6.0 (Canada : Keystone Learning Systems, 2000)
Contents: Introduction to C++ 6, Major components, Object Oriented interfaces, Adding message handlers, Diologs, Modeless dialogs, Single document, More SDI, Using MFC and ActiveX
Professional trainer, instructor: Hany Greiss
Systems requirements: Windows 95 or NT 4.0 or later, 16 MB RAM, 1MB hard disk space, audio card, screen resolution 800X 600 or better
Keywords: Microsoft Visual C++; C++ (Computer program language